2021
DOI: 10.3390/brainsci11030287
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HIC and Hydrostatic Pressure in the Human Head during NOCSAE Tests of American Football Helmets

Abstract: Brain damage is a serious economic and social burden. Contact sports such as American football, are one of the most common sources of concussions. The biomechanical response of the head–helmet system caused by dynamic loading plays a major role. The literature has focused on measuring the resultant kinematics that act on the head and helmet during tackles. However, few studies have focused on helmet validation tests, supported by recent findings and emerging numerical approaches. The future of helmet standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Studies on CM aimed to create new test protocols and metrics to screen the safety of equipment [ 92 , 93 , 97 , 102 ], develop and validate new tools and technologies [ 91 , 96 , 98 , 99 ], study the interaction between neck muscle activation and head impacts [ 95 , 100 ], and study the strain on the brain during practices and games [ 103 ] In Table 4 , data regarding studies related to CM are summarized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on CM aimed to create new test protocols and metrics to screen the safety of equipment [ 92 , 93 , 97 , 102 ], develop and validate new tools and technologies [ 91 , 96 , 98 , 99 ], study the interaction between neck muscle activation and head impacts [ 95 , 100 ], and study the strain on the brain during practices and games [ 103 ] In Table 4 , data regarding studies related to CM are summarized.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the most important branches of research on the studied topic were biomechanical studies regarding injuries encompassing concussions [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ], footwear [ 105 ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dymek et al [70] presented a different approach, where the ICP is investigated in 8 different NOCSAE setups. Additionally, the ICP calculated with the αHEAD model is compared to the Head Injury Criterion (HIC) calculated with the Hybrid III Head-Neck model.…”
Section: Validation Tests With Brain Model Implementationmentioning
confidence: 99%
“…Traumatic brain injury is a severe condition, for which the main cause is excessive mechanical loading during vehicle accidents, sports injuries, violence, or injuries related to everyday activities (e.g., impact with furniture or falls down stairs) [ 27 , 28 , 29 , 30 , 31 ]. Asymmetry within military action zones characterizes actions which differ from those of a stronger enemy, the aim of which being to increase dominance, exploit the weaknesses of the stronger enemy, seize initiative, and gain increased freedom of action [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%